2021
DOI: 10.3389/fphys.2021.648245
|View full text |Cite
|
Sign up to set email alerts
|

Locust Hemolymph Conveys Erythropoietin-Like Cytoprotection via Activation of the Cytokine Receptor CRLF3

Abstract: The cytokine receptor-like factor 3 (CRLF3) is an evolutionary conserved class 1 cytokine receptor present in all major eumetazoan groups. Endogenous CRLF3 ligands have not been identified and the physiological responses mediated by mammalian CRLF3 are poorly characterized. Insect CRLF3 is activated by erythropoietin (Epo) and several related molecules that protect mammalian neurons from stress-induced apoptosis. However, insects neither express Epo nor “classical” Epo receptor. Cell-protective effects of inse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 72 publications
(142 reference statements)
0
11
0
Order By: Relevance
“…Insect primary brain cell culture. Primary neuron cultures were established as previously described 19,32,33,60,73 . In brief, 20 tribolium or 2 locust brains per culture were dissected and collected in Leibowitz 15 medium (Gibco; Life Technologies, Darmstadt, Germany) supplemented with 1% penicillin/streptomycin and 1% amphotericin B (both Sigma-Aldrich, Munich, Germany) (from now referred to as L15 medium).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Insect primary brain cell culture. Primary neuron cultures were established as previously described 19,32,33,60,73 . In brief, 20 tribolium or 2 locust brains per culture were dissected and collected in Leibowitz 15 medium (Gibco; Life Technologies, Darmstadt, Germany) supplemented with 1% penicillin/streptomycin and 1% amphotericin B (both Sigma-Aldrich, Munich, Germany) (from now referred to as L15 medium).…”
Section: Methodsmentioning
confidence: 99%
“…To reduce expression of respective protein, 10 ng/ml dsRNA targeting either one of the genes was added from the beginning of the experiment and renewed with each medium change. Successful interference with protein expression by "soaking RNAi" was previously demonstrated in primary cultured T. castaneum neurons 19,73 . Cells were exposed to hypoxia on day 5 for 36 h (O 2 < 0.3%) before being fixed and analyzed for cell survival.…”
Section: Rna Interference With Ace-1 and Ace-2 Expression In T Castan...mentioning
confidence: 99%
See 2 more Smart Citations
“…This is particular true in the CHD that incorporates the archetypal WSXWS domain, but also extends to residues in the C-terminus, suggesting both are important for function. Indeed, evidence from insect systems suggest that CRLF3 is activated by cytokines, with both exogenous mammalian erythropoietin and an as yet unidentified endogenous cytokine in the hemolymph able to elicit CRLF3-dependent responses ( 57 ), suggesting the CHD is functional in cytokine binding. The insect CRLF3 has also been shown to lie upstream of the JAK-STAT pathway ( 8 ), while mammalian studies have also identified STAT3 as a downstream mediator ( 58 ), actions presumably mediated by the C-terminus of the protein.…”
Section: Discussionmentioning
confidence: 99%